Automatic translation of C/C++ parallel code into synchronous formalism using an SSA intermediate form - Besnard, Loïc; Gautier, Thierry; Moy, Matthieu; Talpin, Jean-Pierre; Johnson, Kenneth; Maraninchi, Florence (Electronic Communications of the EASST, 2009)
We present an approach for the translation of imperative code (likeC, C++) into the synchronous formalism Signal, in order to use amodel-checker to verify properties on the source code. Thetranslation uses SSA as an intermediate formalism, and the GCCcompiler as a front-end. The contributions of this paper withrespect to previous work are a more efficient translation scheme,and the management of parallel code. It is applied successfully onsimple SystemC examples.